2013
DOI: 10.3390/ijms141020793
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transport and Metabolism in Healthy and Osteoarthritic Cartilage

Abstract: Cartilage is an avascular tissue and cartilage metabolism depends on molecule diffusion from synovial fluid and subchondral bone. Thus, nutrient availability is limited by matrix permeability according to the size and charge of the molecules. Matrix composition limits the access of molecules to chondrocytes, determining cell metabolism and cartilage maintenance. Lipids are important nutrients in chondrocyte metabolism and are available for these cells through de novo synthesis but also through diffusion from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 103 publications
3
81
0
3
Order By: Relevance
“…Interestingly, analysis of differentially expressed genes in Dnmt3b LOF chondrocytes showed an enrichment in pathways involved in lipid metabolism. Lipids are important nutrients in chondrocyte metabolism and reports have shown a potential link between OA and disruptions in lipid metabolic processes (42)(43)(44). MethylC-Seq analysis also identified a number of transcription factor binding sites that were enriched in DMRs in Dnmt3b LOF cells.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, analysis of differentially expressed genes in Dnmt3b LOF chondrocytes showed an enrichment in pathways involved in lipid metabolism. Lipids are important nutrients in chondrocyte metabolism and reports have shown a potential link between OA and disruptions in lipid metabolic processes (42)(43)(44). MethylC-Seq analysis also identified a number of transcription factor binding sites that were enriched in DMRs in Dnmt3b LOF cells.…”
Section: Discussionmentioning
confidence: 91%
“…Beside their role in obesity development and subsequent impact on cartilage, 8 dietary lipids have been reported to exert dual effects on inflammation with both pro-and anti-inflammatory effects depending on their structure and metabolism. 9 Joint inflammation contributes to the induction of proteases that degrade cartilage during OA.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the cartilage permeability increases and so does the dietary lipid availability for chondrocytes. 8 In this regard, a growing body of evidence suggests a beneficial effect of dietary poly-unsaturated fatty acids (PUFAs) in rheumatoid diseases such as OA. Cho et al showed that the consumption of n-3 PUFAs rich oil improved joint function and reduced pain in OA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Proteoglycans possess high anionic charge which provides osmotic factors to the matrix which allows cartilage resistance to loading forces [132,133]. Hence, this complex structure enables the articular cartilage to bear compressive loads and also determines how various molecules pass through this matrix.…”
Section: Fa Transport Through Cartilagementioning
confidence: 99%
“…The composition of fatty acid in normal cartilage consists of increased amount of saturated fatty acids and linoleic acid in a matured cartilage and an increased amount of 49 Literature Review ω-3 fatty acids, monounsaturated fatty acids and arachidonic acid in a fetal cartilage [132]. The dietary fatty acids intake can modulate the total fatty acid composition of the cartilage.…”
Section: Fa and Normal Cartilagementioning
confidence: 99%